Hypoxia influences polysome distribution of human ribosomal protein S12 and alternative splicing of ribosomal protein mRNAs - Brumwell, Andrea (RNA, 2020)
Ribosomes were once considered static in their composition because of their essential role in protein synthesis and kingdom-wide conservation. The existence of tolerated mutations in select ribosomal proteins (RPs), such as in Diamond-Blackfan anemia, is evidence that not all ribosome components are essential. Heterogeneity in the protein composition of eukaryotic ribosomes is an emerging concept with evidence that different pools of ribosomes exist with transcript-specificity. Here, we show that the polysome association of ribosomal proteins is altered by low oxygen (hypoxia), a feature of the tumor microenvironment, in human cells. We quantified ribosomal protein abundance in actively translating polysomes of normoxic and hypoxic HEK293 cells by tandem mass tags mass spectrometry. Our data suggest that RPS12 (eS12) is enriched in hypoxic monosomes, which increases the heavy polysome association of structured transcripts APAF-1 and XIAP. Furthermore, hypoxia induced five alternative splicing events within a subset of RP mRNAs in cell lines. One of these events in RPS24 (eS24 protein) alters the coding sequence to produce two protein isoforms that can incorporate into ribosomes. This splicing event is greatly induced in spheroids and correlates with tumor hypoxia in human prostate cancer. Our data suggest that hypoxia may influence the composition of the human ribosome through changes in RP incorporation and the production of hypoxia-specific RP isoforms.